Suppressing Li Dendrite Formation in Li2S‐P2S5 Solid Electrolyte by LiI Incorporation. Issue 18 (12th March 2018) - Han, Fudong; Yue, Jie; Zhu, Xiangyang; Wang, Chunsheng
Abstract: Solid electrolytes have been considered as a promising approach for Li dendrite prevention because of their high mechanical strength and high Li transference number. However, recent reports indicate that Li dendrites also form in Li2 S‐P2 S5 based sulfide electrolytes at current densities much lower than that in the conventional liquid electrolytes. The methods of suppressing dendrite formation in sulfide electrolytes have rarely been reported because the mechanism for the "unexpected" dendrite formation is unclear, limiting the successful utilization of high‐energy Li anode with these electrolytes. Herein, the authors demonstrate that the Li dendrite formation in Li2 S‐P2 S5 glass can be effectively suppressed by tuning the composition of the solid electrolyte interphase (SEI) at the Li/electrolyte interface through incorporating LiI into the electrolyte. This approach introduces high ionic conductivity but electronic insulation of LiI in the SEI, and more importantly, improves the mobility of Li atoms, promoting the Li depositon at the interface and thus suppresses dendrite growth. It is shown that the critical current density is improved significantly after incorporating LiI into Li2 S‐P2 S5 glass, reaching 3.90 mA cm −2 at 100 °C after adding 30 mol% LiI. Stable cycling of the Li‐Li cells for 200 h is also achieved at 1.50 mA cm −2 at 100 °C. Abstract : The dendrite suppression capability of Li2 S‐P2 S5 glass electrolyte can be improved significantly by LiI incorporation, and the 70(0.75Li2 S‐0.25P2 S5 )‐30LiI (LPS30I) electrolyte exhibits the highest capability for dendrite suppression. The critical current density of LPS30I reaches 3.90 mA cm −2 at 100 °C, and the Li/LPS30I/Li cell could cycle 200 h at 1.50 mA cm −2 at 100 °C.